2010
DOI: 10.1177/0002764210376314
|View full text |Cite
|
Sign up to set email alerts
|

In God We Trust: Religiosity as a Predictor of Perceptions of Media Trust, Factuality, and Privacy Invasion

Abstract: The current study brought together two important areas of scholarship in mass communications: media credibility, and religion and the media. Although both areas have been widely investigated by scholars, there have not been many empirical investigations that examine the potential impact of religion on individual perceptions of media credibility. The authors' data analysis revealed mixed evidence for an association between religiosity and perceived media credibility. Although the study did not find consistent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
3
23
1
Order By: Relevance
“…While Golan and Day (2010) found that those who reported that religion guides their daily life activities are characterized by a distrust that the Internet disseminates factual news and a perception of online media as invading privacy, the authors also found some contradictions in their analysis when they looked at the overall importance of religion in their life. By examining religion from a multifaceted perspective, the authors concluded that one's religiosity is a greater predictor of the perception of the Internet as a disseminator of factual news than one's reliance on the Internet for news (Golan & Day).…”
Section: Media Effects Research and Religiositymentioning
confidence: 95%
See 3 more Smart Citations
“…While Golan and Day (2010) found that those who reported that religion guides their daily life activities are characterized by a distrust that the Internet disseminates factual news and a perception of online media as invading privacy, the authors also found some contradictions in their analysis when they looked at the overall importance of religion in their life. By examining religion from a multifaceted perspective, the authors concluded that one's religiosity is a greater predictor of the perception of the Internet as a disseminator of factual news than one's reliance on the Internet for news (Golan & Day).…”
Section: Media Effects Research and Religiositymentioning
confidence: 95%
“…It follows, then, that some mass communications researchers examine the role of religiosity in explaining how media affects society (Golan & Day, 2010;Armfield & Holbert, 2003;Golan, 2002). For example, Golan and Day (2010) found an inverse relationship between the degree to which religion provided guidance on a daily basis and trusting television and newspapers.…”
Section: Media Effects Research and Religiositymentioning
confidence: 99%
See 2 more Smart Citations
“…No single method determines how news consumers perceive news itself as credible (Golan & Day, 2010). However, several researchers have developed various criteria to gauge media credibility (Armstrong & Collins, 2009;Kiousis, 2001;Thorson, Vraga & Ekdale, 2010).…”
Section: Media Credibilitymentioning
confidence: 99%